Cage of ghosts - Rhodes, Jon, 1947-; National Library of Australia ([Canberra] : National Library of Australia, 2007)
Exhibition catalogue gives history of taking the photographs; invitation to opening.
"National Library of Australia 27 September - 25 November 2007".
Includes bibliographic references.
Also available online at
Also available online
Keywords: Rhodes, Jon, -- 1947- -- Exhibitions; Photography in art -- Exhbitions; Aboriginal Australians -- Social life and customs; Historic sites -- Australia; Petroglyphs -- Australia; Tree carving -- Australia; Historic trees -- Australia; Sites - Sites of significance; Art - Rock art - Engraving; Art - Sculpture - Tree carving; Art - Photography; Sites - Scarred trees; Art - Exhibitions; Australian Capital Territory (ACT SI55-16)